Stem Cells for Cardiac Repair: Status, Mechanisms, and New Strategies - Ren Mingliang; Zhang Bo; Wang Zhengguo (Hindawi Limited, 2011)
Faced with the end stage of heart disease, the current treatments only slow worsening of heart failure. Stem cells have the potential of self-renewal and differentiation. It is expected to replace and repair damaged myocardium. But many clinical trials have shown that the stem cell therapy of heart failure is modest or not effective. The possible causes for the limited effects of stem cell in curing heart failure are the stem cells which have been transplanted into the ischemic heart muscle may suffer low survival rate, affected by inflammatory molecules, proapoptotic factor, and lack of nutrients and oxygen, and then the stem cells which home and have been completely transplanted to the site of myocardial infarction become very small. Therefore, through preconditioning of stem cells and appropriate choice of genes for mesenchymal stem cell modification to improve the survival rate of stem cells, ability in homing and promoting angiogenesis may become the newly effective strategies for the application of stem cells therapy in heart failure.